About one approach to monitoring of Interconnected Power System operational condition parameters - Kyrylenko, Oleksandr; Butkevych, Oleksandr; Chyzhevskyi, Volodymyr (Видавництво Львівської політехніки, 2011)
One approach to solving of the most urgent problem of monitoring of Interconnected Power System operational condition parameters consists in the defection of the threat to Interconnected Power System in the form of oscillatory instability is considered.
Keywords: power system operational condition; monitoring; low-frequency oscillation; Phasor Measurement Unit